Acute hepatic ischemic-reperfusion injury induces a renal cortical “stress response,” renal “cytoresistance,” and an endotoxin hyperresponsive state - Zager, Richard A. (American Physiological Society, 2014)
Hepatic ischemic-reperfusion injury (HIRI) is considered a risk factor for clinical acute kidney injury (AKI). However, HIRI's impact on renal tubular cell homeostasis and subsequent injury responses remain ill-defined. To explore this issue, 30–45 min of partial HIRI was induced in CD-1 mice. Sham-operated or normal mice served as controls. Renal changes and superimposed injury responses (glycerol-induced AKI; endotoxemia) were assessed 2–18 h later. HIRI induced mild azotemia (blood urea nitrogen ∼45 mg/dl) in the absence of renal histologic injury or proteinuria, implying a “prerenal” state. However, marked renal cortical, and isolated proximal tubule, cytoprotective “stress protein” gene induction (neutrophil gelatinase-associated lipocalin, heme oxygenase-1, hemopexin, hepcidin), and increased Toll-like receptor 4 (TLR4) expression resulted (protein/mRNA levels). Ischemia caused release of hepatic heme-based proteins (e.g., cytochrome c) into the circulation. This corresponded with renal cortical oxidant stress (malondialdehyde increases). That hepatic derived factors can evoke redox-sensitive “stress protein” induction was implied by the following: peritoneal dialysate from HIRI mice, soluble hepatic extract, or exogenous cytochrome c each induced the above stress protein(s) either in vivo or in cultured tubule cells. Functional significance of HIRI-induced renal “preconditioning” was indicated by the following: 1) HIRI conferred virtually complete morphologic protection against glycerol-induced AKI (in the absence of hyperbilirubinemia) and 2) HIRI-induced TLR4 upregulation led to a renal endotoxin hyperresponsive state (excess TNF-α/MCP-1 gene induction). In conclusion, HIRI can evoke “renal preconditioning,” likely due, in part, to hepatic release of pro-oxidant factors (e.g., cytochrome c) into the systemic circulation. The resulting renal changes can impact subsequent AKI susceptibility and TLR4 pathway-mediated stress.